Teaching students with special needs in inclusive classrooms - Bryant, Diane Pedrotty; Bryant, Brian R.; Smith, Deborah Deutsch (SAGE, 2017)
Using the research-validated ADAPT framework, Teaching Students with Special Needs in Inclusive Classrooms helps future teachers determine how, when, and with whom to use proven academic and behavioral interventions to obtain the best outcomes for students with disabilities. Through clear language and practical examples, authors Diane P. Bryant, Brian R. Bryant, and Deborah D. Smith show how to create truly inclusive classrooms through evidence-based practices and hands-on strategies. This book will provide the skills and inspiration that teachers need to make a positive difference in the educational lives of struggling learners. The text is written to meet the needs of those majoring in general education, special education, and blended teacher education programs.